2024
DOI: 10.1002/eat.24166
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of disordered eating and its association with self‐criticism and self‐compassion

Sarah Marie Paranjothy,
Tracey D. Wade

Abstract: ObjectiveFuture treatments for eating disorders (ED) need to be enhanced by targeting maintaining mechanisms. Literature suggests self‐criticism and self‐critical perfectionism act as key mechanisms exacerbating ED, and self‐compassion protects against self‐criticism. This meta‐analysis examines associations between self‐criticism and self‐critical perfectionism on disordered eating (DE), and reviews how self‐compassion and self‐criticism relate to each other with respect to DE.MethodSearches across three data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 215 publications
0
2
0
Order By: Relevance
“…From 135 studies (total sample size of N = 42,952), they reported small-moderate pooled effect sizes for the crosssectional and prospective relations between these constructs (rs = 0.21-0.58). Paranjothy and Wade (2024) conclude that targeting selfcriticism-potentially through evidence-based treatments augmented with compassion-focused techniques-may be necessary in those who present with highly self-critical response styles established through routine clinical assessments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From 135 studies (total sample size of N = 42,952), they reported small-moderate pooled effect sizes for the crosssectional and prospective relations between these constructs (rs = 0.21-0.58). Paranjothy and Wade (2024) conclude that targeting selfcriticism-potentially through evidence-based treatments augmented with compassion-focused techniques-may be necessary in those who present with highly self-critical response styles established through routine clinical assessments.…”
mentioning
confidence: 99%
“…Conversely, a compassionate response style may negate these effects because it enables the person to treat themselves with kindness and understanding in moments of hardship and perceived inadequacy rather than reacting impulsively. Paranjothy and Wade (2024) conducted several meta-analyses estimating the strength of associations between self-criticism, self-compassion, and disordered eating. From 135 studies (total sample size of N = 42,952), they reported small-moderate pooled effect sizes for the crosssectional and prospective relations between these constructs (rs = 0.21-0.58).…”
mentioning
confidence: 99%